CHINA AND AFGHANISTAN IN THE CONTEXT OF THE NEW SILK ROAD - Editorial Article (Вестник университета)
At present time thanks to the Chinese initiative a unique attempt to reestablish the Ancient Silk Road is carried out. It is supposed that besides implementation of trade activity, there will be an opportunity to exchange knowledge, culture and to develop new technologies more effectively. The prospects of realization of the New Silk Road or One Belt, One Road for Central Asia, Russia, China and Afghanistan as one of the directions - are considered. The positive and negative aspects of this project are emphasized.